2014
DOI: 10.1007/s00590-014-1415-2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a proximal tibial cutting method using the anterior tibial border in TKA

Abstract: The bony landmark method provided a more accurate posterior tibial slope than the conventional method. However, there was no difference in coronal alignment compared with the conventional method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The ankle joint was found to be frequently externally rotated compared with the AP axis of the proximal part of the tibia [31], which caused the distal end of the extramedullary guide to be shifted laterally when placed in front of the center of the ankle joint in cases where the tibia was cut in varus. Sasanuma et al [32] conducted a clinical study examining the accuracy of cutting the proximal tibia using a line connecting the proximal and distal one-third of the anterior border of the tibia. They concluded that there was no difference in coronal alignment between the bony landmark method and the conventional method (within 3°of the target angle: 84% vs. 88%).…”
Section: Discussionmentioning
confidence: 99%
“…The ankle joint was found to be frequently externally rotated compared with the AP axis of the proximal part of the tibia [31], which caused the distal end of the extramedullary guide to be shifted laterally when placed in front of the center of the ankle joint in cases where the tibia was cut in varus. Sasanuma et al [32] conducted a clinical study examining the accuracy of cutting the proximal tibia using a line connecting the proximal and distal one-third of the anterior border of the tibia. They concluded that there was no difference in coronal alignment between the bony landmark method and the conventional method (within 3°of the target angle: 84% vs. 88%).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Nishikawa et al proved that the proximal one-third and the distal one-third of the anterior tibial border were reliable landmarks for the tibial extramedullary alignment guide in TKA 30 . In a clinical trial, Sasanuma et al proved that the proximal and distal one-third of the tibia provides good coronal alignment and better accuracy for the posterior tibial slope compared with the conventional method 13 . In a study by Bilgen et al, the EHL tendon is a reliable anatomical landmark to use with extramedullary guide systems and improves coronal alignment 7 .…”
Section: Discussionmentioning
confidence: 99%
“…To align the extramedullary guides to the mechanical axis of the tibia, a number of bony and soft tissue marker points have been proposed as distal tibial reference points; these include the second metatarsal 6 , the extensor hallucis longus tendon (EHLT) 7–9 , the tibialis anterior tendon (TAT) 10 , the Achilles tendon (AT) 11 , the extensor digitorum longus tendon (EDLT) 11 , and the dorsal pedal artery (DPA) 12 . In addition, in recent years, the lines connecting the proximal and distal thirds of the anterior tibial margin 13 or the medial third of the patellar ligament insertion and the distal quarter of the anterior tibial margin have been used a reference axes during tibial osteotomy 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anterior tibial crest was also reported as a reliable reference for posterior slope of TKA because it is easily palpable during the operation and has less soft tissue. 8,20,21 However, the soft tissue thickness should be considered, although there is less soft tissue in that area. Tsukeoka and Tsuneizumi 9 reported that the accuracy of the sagittal reference using the line tibial cut surface and anterior skin under 20 cm using CT images to reflect the thickness of soft tissue in the anterior tibial crest and the reference was almost similar to that of the mechanical axis in the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%